1999
DOI: 10.1021/ie9901630
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Carbon Steel in the CO2 Absorption Process Using Aqueous Amine Solutions

Abstract: The present study provides comprehensive information on the effects of process parameter variations on the corrosion behavior of carbon steel in CO2 absorption systems using aqueous amine solutions. The process parameters of interest are amine type, concentration of the amine solutions, solution temperature, CO2 loading, and oxygen content. An electrochemical testing technique was used for determining the system corrosiveness in terms of polarization behavior and corrosion rate. The experimental results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
170
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(178 citation statements)
references
References 6 publications
3
170
0
5
Order By: Relevance
“…In terms of corrosion, Veawab et al found that MEA is the most corrosive, followed by AMP and DEA, with MDEA being the least corrosive. 23 These alkanolamines have been used for both research and industrial use, and it is apparent that each absorbent has its own advantages and drawbacks. For a better performance at a lower cost, research and development efforts have been put into improving these absorbents, by combining them or by adding additives.…”
Section: Common Alkanolaminesmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of corrosion, Veawab et al found that MEA is the most corrosive, followed by AMP and DEA, with MDEA being the least corrosive. 23 These alkanolamines have been used for both research and industrial use, and it is apparent that each absorbent has its own advantages and drawbacks. For a better performance at a lower cost, research and development efforts have been put into improving these absorbents, by combining them or by adding additives.…”
Section: Common Alkanolaminesmentioning
confidence: 99%
“…Table 2 lists down some of the hybrid absorbents made from mixing alkanolamine absorbents to improve their characteristics. Veawab et al 23 Thitakamol and Veawab 24 MEA-AMP Absorption column Aroonwilas and Veawab 4 Veawab et al 23 Choi et al 27 Thitakamol Hybrid absorbents have the potential to exceed the performance of single absorbent as proven by Yeon et al 31 They used MEA and TEA as absorbents to remove CO 2 from flue gas in a hollow fiber module membrane contactor. For the hybrid absorbent containing 5wt% TEA and 5wt% MEA, the process operated for 80 h with a CO 2 removal efficiency of 90%-95%.…”
Section: Hybrid Absorbentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acid gas loading is defined as the quantity of acid gas absorbed by a defined quantity of solvent and is often expressed in moles of acid gas per mole of amine. Increasing the acid gas loading increases the corrosivity of amine solutions [18,19,24,25].…”
Section: Acid Gas Corrosionmentioning
confidence: 99%
“…DiEthanolAmine, DEA) slightly less and tertiary amines (e.g. Methyl DiEthanolAmine, MDEA) exhibit the lowest risks of corrosion [18,19,25,[27][28][29][30]. Amine concentration also has an influence on corrosion.…”
Section: Acid Gas Corrosionmentioning
confidence: 99%